Cobalt phosphide-based nanoparticles as bifunctional electrocatalysts for alkaline water splitting. Issue 20 (21st April 2016) - Vigil, Julian A.; Lambert, Timothy N.; Christensen, Benjamin T.
Abstract : Cobalt phosphide-based nanoparticles serve as effective bifunctional electrocatalysts for alkaline water splitting reactions. Abstract : Cobalt phosphide-based nanoparticles serve as effective bifunctional electrocatalysts for alkaline water splitting reactions with activities comparable to more expensive precious metal catalysts.